"Superkiller" mutations suppress chromosomal mutations affecting double-stranded RNA killer plasmid replication in saccharomyces cerevisiae. - Toh-E, A (1980)
Saccharomyces cerevisiae strains carrying a 1.5 x 10(6)-dalton double-stranded RNA genome in virus-like particles (killer plasmid) secrete a protein toxin that kills strains not carrying this plasmid. At least 28 chromosomal genes (mak genes) are required to maintain or replicate this plasmid. Recessive mutations in any of four other chromosomal genes (ski for superkiller) result in enhanced toxin production. We report that many ski- mak- double mutants are able to maintain the killer plasmid, indicating that the SKI products have an effect on plasmid replication. The ski1-1 mutation suppresses (bypasses) all mak mutations tested except mak16-1. A variant killer plasmid is described that confers the superkiller phenotype and, like chromosomal ski mutations, makes several mak genes dispensable for plasmid replication.